Experience of Violence and Health Issues among Female Sex Workers in Kathmandu - Saud, Sarmila Kumari; Aryal, Bhagwan; Ranabhat, Chhabilal (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
Any sex work involving the exchange of money or goods/gifts (i.e. commercial sexual activity) and prostitution in all forms and names are illegal in Nepal. Many issues and violence have been documented as a result of sexual labor in such areas, mainly against female sexual workers (FSWs). This study aimed to explore the lived experiences of violence and the related health issues among FSWs in Kathmandu. A descriptive phenomenological research design was followed where the participants provided their informational experience about violence. The nature of the information was qualitative and subjective, and based on the interpretivism paradigm. The study reveals that verbal aggressions, physical violence, sexual harassment, assault, and other forms of violence are the primary experiences faced by FSWs, along with health issues like STIs, Hepatitis, vaginal infections, backaches, stress, depression, and chronic fatigue. Lived experiences illustrate the opportunities and skills for earning a living via work that could be planned and executed at the federal, provincial, and local levels of government. Similarly, if someone wants to alter their employment or sex trade, rehabilitation is required. It is critical to put in place certain focused measures and policies to safeguard the safety, self-esteem, and financial stability of FSWs.